The performance prediction of current drive by the upgraded neutral beam on EAST. (3rd May 2021) - Wang, Ji; Chen, Jiale; Wu, Bin; Chen, Yuqing; Yang, Zhen; Hu, Chundong; Xie, Yuanlai; Xie, Yahong; Zhang, Xuexi
Abstract: The neutral beamline originally located on Port F is being modified to Port D and the injection direction is changed from clockwise injection (counter-IP) to counterclockwise injection (co-IP) on EAST. The operational quality of the two neutral beamlines will also be upgraded in the following months. The neutral beam current drive (NBCD) of the two upgraded beamlines is substantially improved due to the change from the balanced-injection to the same direction injection with the plasma current by simulation with ONETWO/NUBEAM and TRANSP/NUBEAM codes. Discharge scenarios with the typical parameters are modeled to evaluate NBCD performances for the upgraded beams at beam energy below 70 keV. The maximal NBCD in the prediction exceeds 117 kA which is much higher than the previous level. The simulation results indicate that NBCD after the upgrade are improved with the increase of the beam power and electron temperature Te. The increased plasma density can result in a decrease in NBCD, but it will also lead to a substantial increase in bootstrap current which occupies the dominant fraction of non-induced current. The NBCD can be partly enhanced due to the reduction of the electron shielding effect with the proper increase of Z e f f . These simulation results demonstrate the performances of NBCD after beams upgrade, and can also provide some valuable guidance for future experiments on EAST.